Intra-accumbal blockade of endocannabinoid CB1 receptors impairs learning but not retention of conditioned relief - Bergado Acosta, Jorge R.; Schneider, Miriam; Fendt, Markus (Neurobiology of learning and memory, 2017)
Humans and animals are able to associate an environmental cue with the feeling of relief from an aversive event, a phenomenon called relief learning. Relief from an aversive event is rewarding and a relief-associated cue later induces an attenuation of the startle magnitude or approach behavior. Previous studies demonstrated that the nucleus accumbens is essential for relief learning. Here, we asked whether accumbal cannabinoid type 1 (CB1) receptors are involved in relief learning. In rats, we injected the CB1 receptor antagonist/inverse agonist SR141716A (rimonabant) directly into the nucleus accumbens at different time points during a relief learning experiment. SR141716A injections immediately before the conditioning inhibited relief learning. However, SR141716A injected immediately before the retention test was not effective when conditioning was without treatment. These findings indicate that accumbal CB1 receptors play an important role in the plasticity processes underlying relief learning.